EFEKTIFITAS REHABILITASI PECANDU NARKOTIKA MELALUI TERAPI ISLAMI DI BADAN NARKOTIKA NASIONAL (BNN) BANDA ACEH - Nurdin Bakri; Barmawi Barmawi (Psikoislamedia : Jurnal Psikologi, 2017)
The purpose of this research is to improve the understanding, appreciation and use of Islamic values in all aspects of life. This discussion entitled "The effectiveness of the rehabilitation of narcotic addicts through Islamic therapy in the national narcotics agency (BNN) Banda Aceh". As for the purpose of this research is to know the process of da'wah and efforts and obstacles faced by National Narcotics Agency of Banda Aceh in rehabilitating drug addicts. This research is qualitative with descriptive approach that is doing observation, interview and documentation. The results showed that the implementation of rehabilitation through da'wah in BNN Aceh Province, there are activities that are given are follow religious study activities, listening to spiritual (religious lecture), praying in congregation, reading the Qur'an or short letters, and Do'a together every Monday after inshaa. The tasks of the counselor of rehabilitation through da'wah are: Teaching the science of Islamic religion to the patient, forming a strong Muslim personality, reinforcing the spirit of faith and devotion in the soul, educating patients to beristiqwaan in running the religion, instilling Islamic values through individual approach, Or provide deeds that can awaken drug addicts from the bad habit of taking drugs. The obstacles faced by BNNP Aceh in the rehabilitation of drug addicts are the lack of staff in dealing with victims, the number of victims of narcotics abuse and the non-acceptance of drug abuse victims in the community.